High expression of myocyte enhancer factor 2C (MEF2C) is associated with adverse-risk features and poor outcome in pediatric acute myeloid leukemia: a report from the Children's Oncology Group. Issue 1 (December 2015) - Laszlo, George; Alonzo, Todd; Gudgeon, Chelsea; Harrington, Kimberly; Kentsis, Alex; Gerbing, Robert; Wang, Yi-Cheng; Ries, Rhonda; Raimondi, Susana; Hirsch, Betsy; Gamis, Alan; Meshinchi, Soheil; et al.
Abstract Background Recent studies have identifiedmyocyte enhancer factor 2C (MEF2C ) as cooperating oncogene in acute myeloid leukemia (AML) and suggested a contribution to the aggressive nature of at least some subtypes of AML, raising the possibility thatMEF2C could serve as marker of poor-risk AML and, therefore, have prognostic significance. Methods To test this hypothesis, we retrospectively quantifiedMEF2C expression in pretreatment bone marrow specimens in participants of the AAML0531 trial by reverse-transcriptase polymerase chain reaction and correlated expression levels with disease characteristics and clinical outcome. Results In all 751 available patient specimens, MEF2C messenger RNA (mRNA) was detectable and varied >3000-fold relative toβ-glucuronidase . Patients with the highest relativeMEF2C expression (4th quartile) less likely achieved a complete remission after one course of chemotherapy than the other patients (67 vs. 78 %, P  = 0.005). They also had an inferior overall survival (P  = 0.014; at 5 years 55 ± 8 vs. 67 ± 4 %), inferior event-free survival (P  < 0.001; at 5 years 38 ± 7 vs. 54 ± 4 %), and higher relapse risk than patients within the lower 3 quartiles ofMEF2C expression (P  < 0.001; at 5 years 53 ± 9 vs. 35 ± 5 %). These differences were accounted for by lower prevalence of cytogenetically/molecularly definedlow-risk disease (16 vs. 46 %, P  < 0.001) and higher prevalence ofstandard-risk disease (68 vs. 42 %, P  < 0.001) in patients with highMEF2C expression, suggesting thatMEF2C cooperates with additional pathogenic abnormalities. Conclusions HighMEF2C expression identifies a subset of AML patients with adverse-risk disease features and poor outcome. With confirmation that highMEF2C mRNA expression leads to overexpression of MEF2C protein, these findings provide the rationale for therapeutic targeting ofMEF2C transcriptional activation in AML.